Conceptual Metaphors in Al Mayadeen Regarding Opposition Groups' Attacks on Bashar Al Assad's Regime - Rafli Raharja; Tajudin Nur; Fahmy Lukman (Mauriduna : Journal of Islamic Studies, 2026)
Amid the proliferation of issues covered by the Middle Eastern media, linguistic analysis is crucial for uncovering ideological biases and underlying perspective in the coverage. This study aimed to analyze the conceptual metaphors present in Al Mayadeen’s coverage of opposition group attacks against the Bashar Al Assad regime, as well as to examine the influence of social practices on the channel’s media ideology. The study employed a qualitative descriptive method, with data collected through an observation and note-taking  technique from four news articles between November 28–29, 2024. The data were analyzed using Lakoff and Johnson’s conceptual metaphor theory and Norman Fairclough’s social practice theory. The results revealed that Al Mayadeen shaped perceptions of the conflict through specific metaphors, consistently portraying the opposition as terrorist actors and the regime as the defensive force. The novelty of this study lies in the integration of cognitive semantics and critical discourse analysis to examine one of the 2024 Syrian conflicts. Practically, this research contributes to strengthening media literacy policies and monitoring international journalism to filter out ideological narratives and propaganda in global conflict.